Harnessing Nature’s Resilience: Limonium as a Salt Tolerant Crop in Agriculture - Vashishta, Nishtha; Bhargava, Bhavya (Indian Horticulture, 2025)
Limonium, commonly known as statice or sea lavender, is a globally popular cut flower valued for its vibrant colours, long vase life, and ability to retain beauty when dried. In addition to its ornamental appeal, Limonium shows significant promise in addressing agricultural challenges, particularly soil salinity. As a halophytic plant, it possesses specialized salt tolerance mechanisms such as salt exclusion, ion regulation, osmolyte accumulation, and salt gland secretion. These traits make Limonium ideal for cultivation in saline and degraded soils. With India facing increasing soil degradation—6.72 million ha affected by salinity—Limonium offers a sustainable solution for reclaiming such lands. It is easy to grow, drought-tolerant, and suitable for both fresh and dried floral markets. Moreover, its adaptability and economic potential make it a valuable crop for integrated farming systems. Promoting Limonium cultivation can enhance agricultural resilience, restore soil health, and contribute to a more sustainable and ecologically balanced future.